Effects of Nutritional Status on Semen Characteristics of Kacang Goats - Widiyono, Irkham; Sarmin; Putro, Prabowo Purwono; Astuti, Pudji (Pakistan Journal of Nutrition, 2017)
Background and Objective: Nutritional status of livestock has impact on growth performance and development of reproductive organs. Testicular mass, semen characteristics, spermatogenesis and reproductive hormones can be influenced by feeding levels. This study was conducted to evaluate semen characteristics of Kacang goats given various feeding levels for 24 weeks. Methodology: Nine adult male Kacang goats were divided into 3 feeding groups (G1, G2 and G3). After a 2 week adaptation period, all three groups of goats were fed fully for 8 weeks (full feeding). Then the goats were fed an amount that was 60% (G1), 50% (G2) or 40% (G3) of full feeding levels for the next 8 weeks (restricted feeding). Finally, the goats were refed fully for the last 8 weeks (re-alimentation). Semen samples were collected using an artificial vagina at the end of each feeding period. Results: Full feeding followed by restricted feeding and resumption of full feeding had no significant effects on the ejaculate volume, sperm cell concentration, sperm cell motility and proportion of live sperm values in Kacang goats. Semen parameters were maintained in the physiological range that was normal for Kacang goats. Conclusion: Kacang goats have a good capacity to preserve semen quality at various levels of feeding.